STUDI TENTANG EFEK MEDIA DAN VARIASI SUKROSA TERHADAP PERTUMBUHAN MISELIUM JAMUR TIRAM (PLEUROTUS OSTREATUS) PADA BIBIT F1 - Asia Arifin; Muhammad Rofiq; Baso Manguntungi (CELEBES BIODIVERSITAS : Jurnal Sains dan Pendidikan Biologi, 2022)
Oyster mushrooms are a highly sought-after type of mushroom in the world of agriculture and food due to their delicious flavor and high nutritional value. The growth of oyster mushrooms is significantly influenced by the choice of growth medium and the concentration of sucrose within the medium. This study explores the impact of different growth media and varying sucrose concentrations on the growth of oyster mushroom mycelium in F1 spawn. The research findings indicate that adding 1% sucrose to corn-based medium has a significant positive effect on the growth rate of F1 oyster mushroom mycelium in corn-based medium. Furthermore, in sorghum-based medium, the addition of 5% sucrose also demonstrates a significant impact on the growth of F1 oyster mushroom mycelium. However, the addition of sucrose concentration to sawdust-based medium does not show a significant effect. Based on these research results, it can be concluded that the most suitable medium for the growth of F1 oyster mushroom mycelium is sorghum-based medium due to its superior nutritional and protein content compared to corn and sawdust-based media. Additionally, adding 5% sucrose to sorghum-based medium has been proven to be the most effective in accelerating oyster mushroom growth.